THE ROLE OF LANGUAGE IN NEWS DISCOURSE - Mehriban Monsumova, (International Journal of Innovative Technologies in Social Science, 2022)
In the article, first of all, the concepts of fact and accurate information are disclosed that make up the text of the news. Because an event worthy of news status should be taken as fact. Otherwise, high-quality media will refuse to distribute the material. In addition, it is very important to accurately convey the fact to the public. That is, the maximum proximity of the prepared material to the event accepted as fact increases the accuracy of the information. First of all, a journalist needs to have a perception of the event, to have sufficiently comprehensive information, to correctly understand reality, to have impartiality, objectivity and a sufficient lexical and grammatical base to express his formed opinion. The article also analyzes the important points to pay attention to in the choice of words and sentences in the preparation of news material, depending on the type of media. Thus, different ways of delivering information in different media also have an impact on news materials. For example, the simplicity and clarity of words, the size, and structure of sentences are approached differently, depending on whether the real audience is a reader, listener, or viewer.